2009
DOI: 10.1001/archinternmed.2008.543
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Prevalence of Chronic Low Back Pain

Abstract: Background National or state-level estimates on trends in the prevalence of chronic low back pain (LBP) are lacking. The objective of this study was to determine whether the prevalence of chronic LBP, and the demographic, health-related, and care-seeking characteristics of individuals with the condition have changed over the past 14 years. Methods A cross-sectional, telephone survey of a representative sample of North Carolina (NC) households was conducted in 1992 and repeated in 2006. 4,437 households were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
900
5
22

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,270 publications
(937 citation statements)
references
References 59 publications
(64 reference statements)
10
900
5
22
Order By: Relevance
“…Although 80% of U.S. citizens will experience acute low back pain in their lifetimes, a significant minority will have symptoms persisting >3 months, becoming CLBP. 12 Although the prevalence of all CLBP for ages 24 to 39 years is 4.2%, the prevalence progressively increases with age, reaching 19.6% when patients through age 59 years are included. 13 Because of the methodological challenges of quantitating severe CLBP and the differing definitions used in different studies, prevalence estimates vary, but were estimated at 10.2% in one well executed state-wide study.…”
Section: Alzheimer Disease and Other Dementiasmentioning
confidence: 95%
See 1 more Smart Citation
“…Although 80% of U.S. citizens will experience acute low back pain in their lifetimes, a significant minority will have symptoms persisting >3 months, becoming CLBP. 12 Although the prevalence of all CLBP for ages 24 to 39 years is 4.2%, the prevalence progressively increases with age, reaching 19.6% when patients through age 59 years are included. 13 Because of the methodological challenges of quantitating severe CLBP and the differing definitions used in different studies, prevalence estimates vary, but were estimated at 10.2% in one well executed state-wide study.…”
Section: Alzheimer Disease and Other Dementiasmentioning
confidence: 95%
“…13 Because of the methodological challenges of quantitating severe CLBP and the differing definitions used in different studies, prevalence estimates vary, but were estimated at 10.2% in one well executed state-wide study. 12 Using this estimate and extrapolating to the entire U.S. population, 32 million Americans are estimated to suffer from CLBP. As per patient direct medical incremental costs are estimated at $1,843 in 2014 dollars, 14 the aggregate direct medical costs attributable to CLBP total $59 billion.…”
Section: Alzheimer Disease and Other Dementiasmentioning
confidence: 99%
“…Freburger, et al demonstrated an increase in chronic low back pain from 3.9% (95% CI= 3.4%–4.4%) in 1992 to 10.2% (95% CI= 9.3%–11.0%) in 2006 in a telephone survey of North Carolina households. 97 …”
Section: Clinical Guidelines: Impairment/function-based Diagnosismentioning
confidence: 99%
“…The general population prevalence of CLBP is estimated to be 5.91% in Italy 5 . The prevalence of acute and CLBP in adults doubled in the last decade and continues to increase dramatically in the aging population, affecting both men and women in all ethnic groups 6 . LBP has a significant impact on functional capacity, as pain restricts occupational activities and is a major cause of absenteeism 7– 9 .…”
Section: Low Back Pain Epidemiologymentioning
confidence: 99%